Dam safety emergency action plan: a current practice for hydropower dam in Malaysia - Muda, Rahsidi Sabri; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Abdullah, Fatin Shahira (IOP Publishing Ltd, 2021)
There are currently 104 dams constructed in Malaysia. The dams were built for various purposes; 16 of them were built for hydropower. The dam's reservoir often presents significant risks to downstream areas if a massive downfall release occurs. The enormous downfall could be due to a dam break event, overtopping, and emergency operational release. An incident may occur due to massive flows over a spillway with high-speed discharge or unexpected peak discharge. The obvious impact of the incident is direct to the community in the downstream area. Although there is no dam failure recorded case in Malaysia since the 1900s, the possibility of dam failure occurring is still there. Therefore, the dams must have an emergency action plan (EAP) to prepare the likelihood of the emergency occurrences. This paper aims to explore the EAP practices for dam incident over the region and review the EAP practices of a hydropower dam in Malaysia. Implementing EAP in the emergency response system would minimise the public and environment's impact due to dam failures. The benefit of establishing an EAP is to create better communication and effective responses system among agencies during dam emergency occurrences. This paper revolves around the EAP practices by dam owners in mitigating the risk of dam failure occurrences